Perspectivas del rol de enfermería en cuidados paliativos: una revisión integrativa desde la epistemología del dolor: Perspectives on the role of nursing in palliative care: an integrative review from the epistemology of pain - Espiritu Martinez, Antony Paúl (2025)
This study aimed to critically examine nursing practices, perceptions, and contributions to pain management in palliative care. An in-depth search was conducted using the PICO structured approach in the Scopus, ScienceDirect, and SciELO databases. Boolean operators and pre-specified inclusion and exclusion criteria from the PRISMA flowchart were used. The results were analyzed based on the integrative synthesis proposed by Whittemore et al. The review reveals that nursing is central to palliative care as an active agent of care, extending beyond the pharmacological management of pain. Its involvement combines technical care with a holistic view of suffering and the ethical mediation required to inform clinical recommendations. Systematic pain assessment, committed communication with patients and families, and the integration of techniques with complementary technologies will remain critical for fostering autonomy, well-being, and continuity of care. Through the epistemology of pain, it is concluded that nursing care emerges as a reflective practice that enhances our understanding of suffering beyond biological dimensions. Therefore, it positions nursing as an epistemic-humanistic discipline, where the professional plays a crucial role in preserving dignity, alleviating suffering, and constructing shared meanings that improve the quality of comprehensive care provided in the palliative care process.